"I'll Take Commas for 200": An Instructional Intervention Using Games to Help Students Master Grammar Skills. (March 2014) - Bullard, Sue Burzynski; Anderson, Nancy
Effective writing requires mastering grammar. For journalists, this mastery is critical because research shows poor grammar erodes media credibility. College writing instructors say students do not understand basic grammar concepts, and greater numbers of students are enrolling in remedial writing classes. This quasi-experimental mixed methods study examines whether using games to teach basic grammar skills helps college students understand and retain grammar concepts. It also examines student perceptions of learning.